Floral and reproductive biology of Alpinia purpurata (Vieill.) K. Schum. (Zingiberaceae): An important tropical ornamental plant - França, Rozineide Pereira Alves de; Botini, Auclar Felipe; Koch, Ana Kelly; Caetano, Ana Paula S.; Silva, Ivone Vieira da; Krause, Willian; Silva, Celice Alexandre (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Alpinia spp. play an important ecological role as a source of nectar in the understory of tropical and subtropical forests, where many of these species are common. The perennial species Alpinia purpurata (Vieill.) K. Schum. is native to the tropical rainforests of Asia and has been used as an ornamental cut plant due to its lush inflorescences and post-harvest durability. The internal and external morphology, floral biology, and reproductive system of four A. purpurata cultivars were investigated in order to contribute to studies of genetic improvement of the species. The inflorescence of A. purpurata is terminal, globose, and has flowers protected by colorful and showy bracts. The white flowers are tubular bisexual. The floral anthesis of the four cultivars lasted 9 to 12 h and pollen viability was above 80% throughout the pre-flowering period in all cultivars evaluated. During anthesis, stigma and anther crest were receptive due to the presence of stigmatic fluid. Fruiting of the cultivars was observed after hand cross-pollination, whereas no fruiting was recorded in treatments involving spontaneous self-pollination, hand self-pollination or geitonogamy. Natural pollination induced low fruiting, suggesting low pollinator availability in the studied area. The obligatory xenogamy of A. purpurata is a facilitator for the development of new hybrids for the ornamental plant market.